Towards the Posthuman Here and Now: Posthumanism as a Philosophy of our Time (KULT_online, 2020)
This new monograph by Francesca Ferrando investigates the theoretical and practical implications of onto-epistemological and ethical aspects of the Posthuman condition, supporting it with an updated philosophical frame. Adding to Braidotti’s brand of Posthumanism (i.e. mutually converged Post-humanism and Post-anthropocentrism) a third constitutive element – Post-dualism – Ferrando’s endeavors map a broad range of markers or conceptual nodes where such a paradigm shift could be employed: namely, from the diagnosis and consequent deconstruction of the humanist exclusivist thinking patterns and even certain recent trends coming from the Transhumanist camp – to the proposal of the multiverse of posthuman possibilities, already experienceable here and now.